Kebahagiaan Pasangan Pra-Nikah yang Sudah Melakukan Aktivitas Seksual - Cristofurus Rendy Pancar Pamungkas (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
This study aims to determine the description of happiness of pre-marital couples who have engaged in sexual activity. The method used in this research is a qualitative method, where researchers collect data through interviews with subjects. The subjects in this study are 21-year-old students who have a dating relationship and have engaged in sexual activity with their partners. The subjects of this study amounted to 3 people. The data analysis technique used in this study is through the process of transcribing interviews, reducing data, presenting data, then summarizing the data collected from the research subjects.The results illustrate that the three subjects have different results. The first subject felt that his happiness decreased after sexual activity and the feelings he felt more often were anxiety and fear. The second subject felt his happiness increased and could become closer to his partner after engaging in sexual activity. While the third subject did not feel any difference to his happiness because he did not really consider that sexual activity was the only thing that triggered his happiness. Even so, all three subjects stated that sexual activity can affect the happiness that arises in a dating relationship.